KOMPENSASI MANAJEMEN, REPUTASI AUDITOR,PROFITABILITAS,LEVERAGE, FASILITAS PAJAK DAN MANAJEMEN PAJAK : COMPENSATION MANAGEMENT, AUDITOR'S REPUTATION, PROFITABILITY, LEVERAGE, TAX FACILITIES AND TAX MANAGEMENT - Sidabalok, Windah Lestari; Ratnawati, Vince; Wahyuni, Nita (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2022)
This study expects to examine the impact of the management compensation, auditor reputation, profitability, leverage, and tax facilities on tax management. The populace in this study is manufacturing companies recorded on the Indonesia stock trade for the 2017-2019 period. The sample testing procedure utilized the purposive sampling method. Manufacture companies recorded on the IDX in 2017-2019 totaled 182 companies. There are 60 companies that are included in the sampling criteria with a perception time of 3 years for a sample of 180 manufacturing companies. The scientific technique used is multiple regression using SPSS version 25.0. From the consequences of the test that have been done, the partial regression test ( t-test) shows that compensation management and profitability have a critical adverse consequence on tax management. Auditor reputation variable and tax facilities significantly affect tax management. And leverage factor has no impact on tax management.